Modeling Variability for System Families - Ripon, Shamim Hasnat; Talukder, Kamrul Hasan; Islam Molla, Md. Khademul (Malaysian Journal of Computer Science, 2003)
In this paper, an approach to facilitate the treatment with variabilities in system families is presented by explicitly modelling variants. The proposed method of managing variability consists of a variant part, which models variants and a decision table to depict the customisation decision regarding each variant. We have found that it is easy to implement and has advantage over other methods. We present this model as an integral part of modelling system families.